Removal of Toxic Metals from Aqueous Solutions by Chemically Treated Tur Pods and Banyan Leaves - S. Rajbhoj, Anjali; Gaikwad, S.T.; Sonone, S.R. (Asian Journal of Chemistry, 2016)
Chemically treated tur pods and banyan leaves with formaldehyde and sulphuric acid have been studied as sorbents for removal of toxic metals from aqueous solutions. Effects of time, initial concentration and pH at 30°C have been studied. Sorption capacities have been estimated by Freundlich adsorption models. For tur pods the sorption capacity determined for different heavy metals resulted in the following order: Hg2+ > Cu2+ > Cd2+ > Pb2+ > Zn2+. The percentage of adsorption by banyan leaves is relatively low.